HOW TO GET A BAND 9 OVERALL? - Nurillayev Amirbek Ziyodullo o’g’li; Ahmedova Anorkhon Nasivali qizi (Research Focus International Scientific Journal, 2024)
This article is devoted to the study of IELTS (International English Language Testing System) and how to get the highest score from it and it is going to be fully analyzed why it’s global all around the world? Moreover, it includes much more information about niners (people who got 9 in overall) in Uzekistan, their lifestyles and some of their quotes about studying.